Comparative Study of Switching Energy Losses between Si Pin and SiC Schottky Diodes - Yahaya, Nor Zaihar; Koo, Choon Chew (2004)
This paper is to compare the switching energy losses of the Silicon Carbide Schottky diode with the Silicon PiN diode. The comparison is done using an Inductive Load Chopper circuit simulated with Pspice, a type of circuit analysis software. Both diode models used for the simulation are from Infineon; the Silicon Carbide Schottky (SDP04S60, 4A/600V) and Silicon PiN (IDP06E60, 6A/600V).